Case report: Long-term partial response of apatinib plus paclitaxel as second-line therapy in a patient with metastatic gastric cancer - Fu, Shengya; Li, Linjuan; Li, Xiaofen; Wu, Qiang; Wang, Xiaohui; Huang, Yan; Hu, Haoyue; Cao, Dan (Frontiers in Pharmacology, 2022)
Gastric cancer is the second most prevalent cancer and the second leading cause of cancer-related death in China. The prognosis of metastatic gastric cancer is poor with a median overall survival of 8 to 10 months. Apatinib, an oral small-molecule, selective vascular endothelial growth factor receptor-2 tyrosine kinase inhibitor, is approved as third-line or subsequent therapy for gastric cancer in China. Several recent small-scale studies and case reports showed that it may be great help in improvement of prognosis as second-line treatment in patients with advanced or metastatic gastric cancer. Here, we present a case of advanced gastric adenocarcinoma with multiple hepatic metastases who was treated with apatinib plus paclitaxel as second-line therapy, realized a long progression-free survival of 37 months. Until January 29, 2022, the disease remains an efficacy of partial response. We believe that the good outcome of this case is not an accident, because of the typically hyper-vascular of his liver metastases, the treatment toxicities of hypertension and proteinuria, all may be potential predictive biomarkers for anti-angiogenic treatments.